The complex relationship between depression and progression to incident cognitive impairment across race and ethnicity. Issue 12 (25th February 2022) - Babulal, Ganesh M.; Zhu, Yiqi; Roe, Catherine M.; Hudson, Darrell L.; Williams, Monique M.; Murphy, Samantha A.; Doherty, Jason; Johnson, Ann M.; Trani, Jean‐Francois
Abstract: Introduction: We examined baseline differences in depression and antidepressant use among cognitively normal older adults in five ethnoracial groups and assessed whether depression predicted a faster progression to incident cognitive impairment across groups. Methods: Data from the National Alzheimer's Coordinating Center (n = 8168) were used to examine differences between non‐Hispanic Whites (nHW), African Americans (AA), Hispanics, Asians, and American Indian and Alaskan Natives in cross‐sectional and longitudinal models. Results: AA had a lower risk of depression compared to nHW at baseline. No statistical interactions were noted between ethnoracial groups and depression. However, depression independently predicted a faster progression to incident cognitive impairment. Hispanics and Asian participants had a higher hazard for progression compared to nHW. Discussion: Previously established risk factors between depression and dementia were not found among AA and nHW participants. The relationship between depression and ethnoracial groups is complex and suggests differential effects on progression from cognitive normality to impairment.